Safety and efficacy of renal sympathetic denervation: a 9-year long-term follow-up of 24-hour ambulatory blood pressure measurements - Vogt, Alexander; Dutzmann, Jochen; Nußbaum, Michael; Hoyer, Daniel; Tongers, Jörn; Schlitt, Axel; Sedding, Daniel; Plehn, Alexander (Frontiers in Cardiovascular Medicine, 2023)
Background: Renal sympathetic denervation (RDN) has been shown to lower arterial blood pressure in presence as well as in absence of antihypertensive medication in an observation period of up to 3 years. Long-term results beyond 3 years are scarce. Methods: We performed long-term follow-up in patients who were previously enrolled in a local renal denervation registry and underwent radiofrequency RDN using the Symplicity Flex® renal denervation system between 2011 and 2014. Patients received assessment by 24-hour ambulatory blood pressure measurement (ABPM), medical history, and laboratory tests to evaluate renal function. Results: 24h ambulatory blood pressure readings were available for 72 patients at long-term follow-up (9.3 years [IQR 8.5-10.1]). We found a significant reduction of ABP from 150.1/86.1±16.9/12.0 mmHg at baseline to 138.3/77.1±16.5/11.1 mmHg at long-term follow-up (FU) (P<0.001 for both systolic and diastolic ABP). The number of antihypertensive medications used significantly decreased from 5.4±1.5 at baseline to 4.8±1.6 at long-term follow-up (P<0.01). Renal function showed a significant but expected age-associated decrease in eGFR from 87.8 (IQR 81.0-100.0) to 72.5 (IQR 55.8-86.8) ml/min/1.73m² (P<0.01) in patients with an initial eGFR > 60ml/min/1.73m², while a non-significant decrease was observed in patients with initial eGFR <60ml/min/1.73m² at long-term follow-up (56.0 [IQR 40.9-58.4] vs. 39.0 [IQR13.5-56.3] ml/min/1.73m²). Conclusions: RDN was followed by a long-lasting reduction in blood pressure with a concomitant reduction in antihypertensive medication. No negative effects could be detected, especially with regard to renal function.